Personal and Organizational Spirituality as a Buffer Against the Negative Effect of Supervision on Job and Life Satisfaction - 알리아 나즈; 백연정 (리더십연구, 2023)
Abusive supervision is a toxic job demand that can ruin employees’ professional and personal lives. Based on job demands– resources theory, the present study introduces a new job resource that attenuates the negative effects of abusive supervision on job and life satisfaction: spirituality. In so doing, this study distinguishes personal spirituality— or an individual orientation to value, experience, or express an inner life, sense of community, and meaningfulness in life— from organizational spirituality— or an organizational feature that encourages its members to value and experience inner life, develop a connection within and outside the organization, and seek meaning and purpose at work. Using a multi-wave survey of 197 employees, we found that the negative relationship between abusive supervision and work engagement was weaker at a high rather than low level of organizational spirituality. However, the moderating effect of spirituality was not significant for personal spirituality. In addition, work engagement was found to mediate the interaction effect between abusive supervision and organizational spirituality on both job satisfaction and life satisfaction.
Keywords: abusive supervision; personal spirituality; organizational spirituality; work engagement; employee satisfaction; 비인격적 감독; 개인영성; 조직영성; 직무열의; 직원만족